2020
DOI: 10.1371/journal.pone.0243226
|View full text |Cite
|
Sign up to set email alerts
|

Law and (rec)order: Updating memory for criminal events with body-worn cameras

Abstract: Body-worn video is increasingly relied upon in the criminal justice system, however it is unclear how viewing chest-mounted video may affect a police officer’s statement about an event. In the present study, we asked whether reviewing footage from an experienced event could shape an individual’s statement, and if so, whether reporting before reviewing may preserve an officer’s original experience. Student participants (n = 97) were equipped with chest-mounted cameras as they viewed a simulated theft in virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 87 publications
0
9
2
Order By: Relevance
“…The predicted increase in accuracy in the watch first condition (H3) also did not transpire. This contrasts with Adams et al’s (2020) findings that students who had reviewed BWC footage provided significantly more complete and accurate reports of a virtual-reality crime, but with fewer off-camera details, than students who had not reviewed the footage. Potential explanations for the lack of statistically significant between-participants differences in the present study may be found in methodological features, such as the variation in incident duration or the short delay between the incident and footage review, which we address in the “Limitations” section.…”
Section: Discussioncontrasting
confidence: 89%
“…The predicted increase in accuracy in the watch first condition (H3) also did not transpire. This contrasts with Adams et al’s (2020) findings that students who had reviewed BWC footage provided significantly more complete and accurate reports of a virtual-reality crime, but with fewer off-camera details, than students who had not reviewed the footage. Potential explanations for the lack of statistically significant between-participants differences in the present study may be found in methodological features, such as the variation in incident duration or the short delay between the incident and footage review, which we address in the “Limitations” section.…”
Section: Discussioncontrasting
confidence: 89%
“…The notion that “video ‘tells us exactly what happened’ [is] an ideology which extends throughout the justice system” (Adams et al, 2020, p. 2). Indeed, the “new transparency encourages beliefs in images speaking for themselves, in cameras as mechanically objective witnesses, and in information as self‐evident” (Brucato 2015, p. 44), a view adopted by the Supreme Court of the United States in a case involving dashboard camera video of a high‐speed chase (Scott v. Harris, 550 U.S. 372 [2007]; see Kahan et al, 2009) and in other federal courts (see, e.g., Fields v. Philadelphia, 862 F.3d 353, p. 359 [3rd Cir.…”
Section: Police Visibility and The Power Of Police Imagesmentioning
confidence: 99%
“…8–9). In the current moment, “the only evidence more powerful than ‘I saw it with my own eyes’ is ‘I have it recorded on camera’” (Adams et al, 2020, p. 1). As the famous Rodney King trial (in which defense attorneys successfully re‐framed the narrative surrounding the beating of a black man by several Los Angeles police officers by playing the video in slow motion and offering officer‐friendly explanations of the depicted events [Brayne et al, 2018; Goodwin, 1994; Stuart, 2011]) demonstrated, the interpretation of video evidence is not always a straightforward, objective task.…”
Section: Police Visibility and The Power Of Police Imagesmentioning
confidence: 99%
See 2 more Smart Citations